L’orobe (Vicia ervilia L. Willd.) au Maroc - Salama El Fatehi; Mohammed Ater (Revue d'ethnoécologie)
In this contribution, we will present some aspects of the history, nomenclature and uses of the culture of the bitter vetch (Vicia ervilia L. Willd.). Although this crop is currently considered to be minor and used only in animal feed, this has not always been the case. At certain times in history, the cultivation of the bitter vetch was more important and had a significant place among the cultivated legumes. Although it was little appreciated, it was used in human food and was part of the traditional pharmacopoeia. The excessive marginalization of the culture and consumption of the bitter vetch is relatively recent. The value of conservation of this type of resource is discussed in the light of the search for sustainability and resilience of the agroecosystems in the face of global changes.